Influence of insectocompost obtained by cultivation of the during beetle Ulomoides dermestoides on the ecological-trophic composition and development of soil and phytoparasitic nematodes - Zh. V. Udalova; N. N. Butorina; N. A. Ushakova; S. V. Zinovieva (Российский паразитологический журнал, 2024)
The purpose of the research is to study the effect of insect compost obtained as a result of the vital activity of insects of the Coleoptera order Ulomoides dermestoides on the quantitative and qualitative composition of soil nematodes of various ecological and trophic groups, as well as on the morphological and physiological state of plants and infection of tomato plants with root-knot nematodes.Materials and methods. Under laboratory conditions, soil containing a diverse fauna of nematodes was treated with 1% dry and 0.5; 0.75 and 1% aqueous solutions of biocompost. Insect compost was obtained by keeping the U. dermestoides on a dry nutrient mixture. Then a mixture of lawn grasses was sown in the ground. After 30 days, the composition of nematodes was analyzed. The ability of insect compost to suppress parasitic nematode species was studied using the tomato-knot nematode model system. Tomatoes were infected with Meloidogyne incognita at a rate of 500 larvae (J2) per plant and simultaneously treated with a 0.5% aqueous biocompost solution.Results and discussion. The insect compost U. dermestoides has an effect on quantitative and qualitative indicators in the community of soil nematodes, increasing the number of predatory and saprobiotic nematodes and displacing parasitic ones. And due to the content of various biologically active compounds, it affects the development of rootknot nematodes in tomato roots. When tomatoes are treated with an aqueous solution of insect compost, the infection score and the number of nematodes that penetrate the roots are reduced. The introduction of compost when growing a mixture of lawn grasses and tomatoes can improve the condition of the plants.